2014
DOI: 10.1016/j.ijrobp.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Observational Research Using Large Data Sets in Radiation Oncology

Abstract: The radiation oncology community has witnessed growing interest in observational research conducted using large-scale data sources such as registries and claims-based datasets. With the growing emphasis on observational analyses in health care, the radiation oncology community must possess a sophisticated understanding of the methodological considerations of such studies in order to evaluate evidence appropriately to guide practice and policy. Because observational research has unique features that distinguish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 111 publications
4
44
0
Order By: Relevance
“…Last, PSM minimizes bias by balancing confounders based on observed characteristics. It does not eliminate the possibility that outcomes are influenced by unobserved, and thus potentially unbalanced, covariates …”
Section: Discussionmentioning
confidence: 99%
“…Last, PSM minimizes bias by balancing confounders based on observed characteristics. It does not eliminate the possibility that outcomes are influenced by unobserved, and thus potentially unbalanced, covariates …”
Section: Discussionmentioning
confidence: 99%
“…Another weakness of the NCDB is that it is not population based but hospital based, taken from the institutions where patients present for diagnosis and management, thus hampering the generalizability of NCDB cohorts, all of whom are patients treated at accredited hospitalsVpresenting a potential selection bias for higher-quality patient care and outcomes. 16 In conclusion, this hospital-based retrospective analysis of patterns of care in stage I HIR EC demonstrates variability in how consistently adjuvant RT is given to these patients. The National Comprehensive Cancer Network guidelines allow for observation in such patients because local recurrences can be salvaged and because randomized trials have yet to show any overall survival benefit.…”
Section: Discussionmentioning
confidence: 79%
“…There are many warnings cited in the 11,13,16,17 For example, a study in 2014 on International Classification of Diseases, Ninth Revision (ICD-9) codes for patients undergoing lumbar fusions showed that 48% of the cases did not have a primary diagnosis code to reflect the primary indication for surgery. There are many warnings cited in the 11,13,16,17 For example, a study in 2014 on International Classification of Diseases, Ninth Revision (ICD-9) codes for patients undergoing lumbar fusions showed that 48% of the cases did not have a primary diagnosis code to reflect the primary indication for surgery.…”
Section: Limitations Of Current Large Databasesmentioning
confidence: 99%